Optimalisasi Dikmas Lantas Mengurangi Pelanggaran Lalu Lintas - Pasla G M Simanjuntak (Indonesian Journal of Police Studies, 2020)
In the last 3 years, drugs crime is the most common case in the Bogor City area with 561 cases. Binmas Bintibmas unit has a role in efforts to tackle drug cases among high school students with guidance and counseling. This study is to analyze and describe the efforts and factors that influence the implementation of binluh by the bintibmas unit. Research location in Bogor City Polresta with the focus of the bintibmas unit. This study using qualitative methods with descriptive analysis techniques. Using triangulation (Moleong;2006:330) of data which is sources, theories and techniques adn using primary, secondary and tertiary data sources. Data validity including data reduction, data present, conclusion making and verification. This research uses management function theory, management element theory and Force Field Analysis theory and effort concept, binluh concept, drug abuse concept and bintibmas concept. The sub-optimal implementation of binluh carried out by the bintibmas unit is analyzed from the planning function, preparing the material to determine binluh targets, organizing, preparing competent officers, implementation and control, assessment and monitoring in binluh activities. In the implementation factor that influence binluh are internal factors that influence that are the factors of people, budget, infrastructure and methods of binluh and external factors are community awareness and factors of other functions also the effort doing with coaching and relationship and work procedures. The conclusion is binluh inhibiting factors carried out by the bintibmas unit are member competencies, extension materials, budgets, cooperation with other functions and agencies, binluh target determination and binluh methods.